Fluticasone Propionate Suppresses Poly(I:C)-Induced ACE2 in Primary Human Nasal Epithelial Cells - Nakazono, Akira; Nakamaru, Yuji; Ramezanpour, Mahnaz; Kondo, Takeshi; Watanabe, Masashi; Hatakeyama, Shigetsugu; Kimura, Shogo; Honma, Aya; Wormald, P. J.; Vreugde, Sarah; Suzuki, Masanobu; Homma, Akihiro (Frontiers in Cellular and Infection Microbiology, 2021)
Background From the first detection in 2019, SARS-CoV-2 infections have spread rapidly worldwide and have been proven to cause an urgent and important health problem. SARS-CoV-2 cell entry depends on two proteins present on the surface of host cells, angiotensin-converting enzyme 2 (ACE2) and transmembrane protease serine 2 (TMPRSS2). The nasal cavity is thought to be one of the initial sites of infection and a possible reservoir for dissemination within and between individuals. However, it is not known how the expression of these genes is regulated in the nasal mucosa. Objective In this study, we examined whether the expression of ACE2 and TMPRSS2 is affected by innate immune signals in the nasal mucosa. We also investigated how fluticasone propionate (FP), a corticosteroid used as an intranasal steroid spray, affects the gene expression. Methods Primary human nasal epithelial cells (HNECs) were collected from the nasal mucosa and incubated with Toll-like receptor (TLR) agonists and/or fluticasone propionate (FP), followed by quantitative PCR, immunofluorescence, and immunoblot analyses. Results Among the TLR agonists, the TLR3 agonist Poly(I:C) significantly increased ACE2 and TMPRSS2 mRNA expression in HNECs (ACE2 36.212±11.600-fold change, p<0.0001; TMPRSS2 5.598±2.434-fold change, p=0.031). The ACE2 protein level was also increased with Poly(I:C) stimulation (2.884±0.505-fold change, p=0.003). The Poly(I:C)-induced ACE2 expression was suppressed by co-incubation with FP (0.405±0.312-fold change, p=0.044). Conclusion The activation of innate immune signals via TLR3 promotes the expression of genes related to SARS-CoV2 cell entry in the nasal mucosa, although this expression is suppressed in the presence of FP. Further studies are required to evaluate whether FP suppresses SARS-CoV-2 viral cell entry.